2021
DOI: 10.1007/s10570-021-04260-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cationic cotton through reaction with different polyelectrolytes

Abstract: Graphic abstract Cationization of cotton fabrics was performed by exhaustion procedure utilizing four different reagents provided with quaternary ammonium groups: poly diallyldimethylammonium chloride (PDDACl), poly acrylamide-co-diallyldimethylammonium chloride (PAcD), poly[bis(2-chloroethyl) ether-alt-1,3-bis[3-(dimethylamino)propyl]urea] quaternized (P42) and 3-chloro-2-hydroxypropyl trimethyl ammonium chloride (CHPTAC). Pretreated samples were dyed using Reactive Red 195 dye. The cationic fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…10.7% remaining in the dyebath), of which 80.6% (F) was fixated to the CellReg/GTAC_1.5 fibers. Therefore, the cationization of the regenerated cellulose fibers improved both the dye exhaustion and dye fixation because this anionic reactive dye can simultaneously interact with the hydroxyl and the tetraalkylammonium groups of the modified cellulose samples [21]. Furthermore, it is important to mention that Cell-Reg/GTAC_1.5 generated the maxima values of dye exhaustion and dye fixation, despite displaying the lowest DS value, probably because of the conjunction of its fibrillar structure, greater surface area and higher availability of the surface cationic groups when compared with the other two modified samples with a film-like morphology.…”
Section: Dye Uptake Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…10.7% remaining in the dyebath), of which 80.6% (F) was fixated to the CellReg/GTAC_1.5 fibers. Therefore, the cationization of the regenerated cellulose fibers improved both the dye exhaustion and dye fixation because this anionic reactive dye can simultaneously interact with the hydroxyl and the tetraalkylammonium groups of the modified cellulose samples [21]. Furthermore, it is important to mention that Cell-Reg/GTAC_1.5 generated the maxima values of dye exhaustion and dye fixation, despite displaying the lowest DS value, probably because of the conjunction of its fibrillar structure, greater surface area and higher availability of the surface cationic groups when compared with the other two modified samples with a film-like morphology.…”
Section: Dye Uptake Testsmentioning
confidence: 99%
“…Reactive Blue 19 (F = 81-82%). Furthermore, Correia et al [21] extensively studied the effect of four different (poly)electrolytes containing quaternary ammonium groups, including GTAC, on the dyeing process of cotton with the reactive red 195 dye. The authors concluded that the cationization of cotton with GTAC was the most advantageous in terms of dye fixation and exhaustion since it generated the lowest mass of residual dye in both exhaustion and washing baths [21].…”
Section: Dye Uptake Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 To avoid these disadvantages, cationic polymers show good application prospects in salt-free reactive dyeing because of their higher affinity to cellulosic fibers, and the studied polymers include poly(diallyldimethylammonium chloride) (PDDACl), chitosan, poly(acrylamide-co-diallyldimethylammonium chloride) (PAcD), quaternized poly[bis(2-chloroethyl)ether-alt-1,3-bis [3-(dimethylamino)propyl]urea], poly(hexamethylene biguanide) (PHMB), poly(acryloxyethyl trimethylammonium chloride) (PAOTAC), tertiary amine cationic polyacrylamide (TACPAM), polyamino carboxylic acids (PACAs), cationic starch (Q-TAC), keratin, betaine, and ovalbumin. [19][20][21][22][23][24][25][26][27][28][29] For example, Oliveira et al 30 used chitosan and PDDACl to modify cotton and polyester blended fabrics, and high dyebath exhaustion and excellent color strength were obtained for dyeing of the modified fabrics with dispersed/reactive dyes. Correia et al 19 found that PDDACl presented results similar to the commercial reagent CHPTAC, but the concentration of cationic agent was 20 g L −1 and high pH was employed to increase the interaction of cotton fiber with the cationic agent.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29] For example, Oliveira et al 30 used chitosan and PDDACl to modify cotton and polyester blended fabrics, and high dyebath exhaustion and excellent color strength were obtained for dyeing of the modified fabrics with dispersed/reactive dyes. Correia et al 19 found that PDDACl presented results similar to the commercial reagent CHPTAC, but the concentration of cationic agent was 20 g L −1 and high pH was employed to increase the interaction of cotton fiber with the cationic agent. Wang et al 31 recently treated cotton fabric with 2-4 g L −1 of PHMB by the pad-drycure method, and the treated fabric could be dyed with acid dyes, which is regarded as a process involving zero discharge of dye wastewater and 100% utilization of dyes, but the underlying mechanism was not confirmed.…”
Section: Introductionmentioning
confidence: 99%